Selection of technique for yeast collection from the canine oral cavity (Research, Society and Development, 2022)
The first step in the collection of microbiological samples is the selection of techniques to be used, which guarantees a higher yield of microorganisms and a more assertive identification of them. Considering the scarcity of studies related to the presence of yeasts in the canine oral cavity, this work broached the comparison between techniques of collection of the canine oral cavity already used and not yet used in 18 dogs treated at the Hospital Veterinário de Animais de Companhia (UFRRJ) and private clinics of the adjacencies. The purpose of this comparative study is to stimulate research for the standardization of the canine oral microbiome and to expand knowledge about the yeasts present in this microbiota. Therefore, the following instruments were compared for sample collection: swab, filter paper and commercial human toothbrush. The technique that demonstrated the greater use of the sample and less microbial loss was the use of a toothbrush. Therefore, it was concluded that the most effective collection of yeasts from the canine oral cavity was the commercial human toothbrush, recommended for future trials.